A novel seawater and sea sand concrete filled FRP-carbon steel composite tube column: Concept and behaviour. (15th August 2020) - Zhang, Yirui; Wei, Yang; Bai, Jiawen; Wu, Gang; Dong, Zhiqiang
Highlights: A novel seawater and sea sand concrete filled composite tube (SFSCT) was proposed. The column consists of FRP, steel tube, FRP and seawater and sea sand concrete. The confinement mechanism of SFSCT columns was investigated. The axial mechanical properties of SFSCT columns are improved by both confinement. Abstract: A novel type of seawater and sea sand concrete (SSC)-filled FRP-carbon steel composite tube (SFSCT) column composed of FRP-carbon steel composite tubes and core-filled SSC is proposed. The FRP carbon steel composite tube is made by wrapping FRP sheets around the inner and outer walls of steel tubes to isolate the transport of chloride ions from the external corrosive environment and the internal SSC, respectively. A total of 36 SFSCT columns were tested under axial compression to investigate the axial compressive performance. The test parameters include the FRP thickness, FRP type and steel tube thickness. The test results show that internal FRPs and external FRPs can work together and effectively improve the bearing and deformation capacities of the structure under axial compression. Compared with concrete-filled steel tube (CFST) columns, with different numbers of FRP wrapping layers, the strength of the SFSCT columns can be increased by 11.7–66.5%. The confinement effect of CFRP is better than that of BFRP. Compared with the steel tube thickness, the FRP type and FRP thickness have a more significant influence on the stress-strain behaviour of SFSCT columns.